2022
DOI: 10.18326/ijtihad.v22i2.155-176
|View full text |Cite
|
Sign up to set email alerts
|

Problems with the Islamic legal system regarding child marriages in Indonesia during the covid-19 pandemic period

Abstract: The high number of child marriages during the Covid-19 pandemic period poses problems related to the Islamic legal system in Indonesia. This study aims to describe the problems of the Islamic legal system regarding the phenomenon of child marriages during the pandemic period in Indonesia. This paper is the result of a qualitative research with a socio-legal analysis approach, that is based on Friedman Hayden's legal system theory. The results of the study show that there are three substantial problems with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…This proves that the aspect of spiritual development is the main component that needs to be emphasized in developing the self-identity of delinquents. Spiritual development is a pillar for physical, emotional, intellectual, and social well-being in adolescents (Paad et al, 2021;Lathifah et al, 2022).…”
Section: Priority Flow For Main Componentsmentioning
confidence: 99%
“…This proves that the aspect of spiritual development is the main component that needs to be emphasized in developing the self-identity of delinquents. Spiritual development is a pillar for physical, emotional, intellectual, and social well-being in adolescents (Paad et al, 2021;Lathifah et al, 2022).…”
Section: Priority Flow For Main Componentsmentioning
confidence: 99%
“…The reported case of child sexual abuse above underscores the alarming scenario where the victims are young adolescents, aged 13-14 years, with the perpetrator being a 54-year-old teacher. This disturbing trend, as Lathifah et al (2022) note, highlights the prevalence of such abuse in seemingly safe spaces, like schools. Echoing this, Altinyelken & Le Mat (2018) found that a significant 54.3% of child sexual abuse incidents take place in school settings, implicating teachers as the primary offenders.…”
Section: Article Historymentioning
confidence: 99%